Financial planning in the profitability of the company Inversiones y Multiservicios Vida MYCE S.R.L. Ayacucho, 2023 - Llacccho Sulca, Miriam Linda (2025)
This research analyzes the impact of financial planning on the profitability of the company Inversiones y Multiservicios Vida MYCE S.R.L. Specific objectives have been planned: to analyze financial strategies, financial projections and financial control in the profitability of the company. The methodology used was basic, with a qualitative approach and a case study design, where interviews were conducted with six participants, including the manager and finance experts, which allowed a multidimensional exploration of the phenomenon. The results obtained show that robust financial planning, which includes the implementation of a contingency fund and the analysis of historical trends, is crucial to improve economic stability. In addition, it was identified that product diversification and effective cash flow management are essential to maximize income and minimize risks. The importance of a budget management system and the need to strengthen interdepartmental communication was highlighted. Finally, the conclusions indicate that adequate management of economic resources can transform negative profitability margins into positive ones. The research highlights the relevance of strategies such as rigorous cost control and inventory optimization, suggesting that future research explore the impact of technology and loyalty strategies on the profitability of the hardware sector.